SUPERVISI PEMERIKSAAN DAN PENYEMBELIHAN HEWAN QURBAN YANG ASUH DI GAMPONG TUNGKOP KECAMATAN DARUSSALAM KABUPATEN ACEH BESAR - Makmur, Ali; Jalaluddin, Muhammad; Yulisma, Rika; Sofyan, Hamny; Wahyuni, Sri; Isky, Saiful; Novita, Andi; ., Daniel; Fahrezi, Muhammad Gilbran (Universitas Nusa Cendana, 2024)
Personal hygiene is an action taken to maintain cleanliness and health for an individual’s physical and mental well-being. Good personal hygiene practices minimize the entry of microorganisms, thereby reducing the risk of individuals contracting diseases. ASUH, which stands for Safe, Healthy, Whole, and Halal, can be used as an indicator of food suitability for processing and human consumption. This community service activity aimed to supervise the effort to ensure the eligibility of sacrificial animals in Gampong Tungkop, Darussalam District, Aceh Besar Regency, through ante-mortem and post-mortem examinations. The animals examined included 24 cows and 6 goats ready for slaughter. The examinations consisted of ante-mortem examination, which covered the general condition, teeth, health status, eye mucosa, anus, absence of defects, sufficient age, not emaciated, and male gender. Post-mortem examination, which assessed the condition of the meat and visceral organs, including the liver (hepar), small intestine (intestinum tenue), large intestine (intestinum crassum), stomach (ventriculus), kidneys (ren), lungs (pulmo), spleen (lien), and heart (cor). Observations showed that the eye mucosa color of the examined cows and goats was generally pink, indicating normal conditions. All cows and goats examined were healthy and had perfect physical conditions (no defects). The post-mortem examination results showed that the meat, stomach, spleen, heart, lungs, and kidneys were in normal condition. However, endoparasites of the Fasciola hepatica type were found in the livers of five slaughtered cows. Health conditions of the supervised cows and goats met the requirements for sacrificial animal slaughter.